Menelisik Variasi Dialek Bugis Bone Selatan Dalam Memutus Deskrepansi Interdialektal Perspektif Geososiolinguistik Chambers Trudgill - Halal, Andi Hartina; Srimularahmah, Andi; Idris, Muhammad; Taufan Asfar, Andi Muhammad Irfan; Akbar Asfar, Andi Muhammad Iqbal (LPPM Universitas Dharma Andalas, 2026)
Language is dynamic and exhibits variation due to differences in the social, geographical, and cultural backgrounds of its speakers, one of which is manifested in dialects that function as markers of socio-cultural identity within a community. This study aims to examine the variation of Bugis dialects in South Bone using a geosociolinguistic approach. This study employed a mixed-method approach with a sequential explanatory design. The population consisted of communities in the Kahu, Libureng, and Bontocani districts, with samples selected purposively. Quantitative data were collected using Likert-scale questionnaires, while qualitative data were obtained through in-depth interviews and participatory observation. Data sources included both primary and secondary data. Quantitative data were analyzed using descriptive statistics, including frequency distributions and percentages, whereas qualitative data were analyzed thematically. The results indicate that the community demonstrates a very high level of acceptance of Bugis dialect variation. These variations are evident in phonetic, lexical, and intonational aspects, with distinct characteristics in each region. Kahu tends to use a more neutral dialect, Libureng exhibits strong phonetic and intonational features, while Bontocani maintains more conservative phonetic characteristics due to geographical factors. These variations are influenced by geographical, social, cultural, educational, economic, and modernization factors. Thus, dialect variation is not perceived as a barrier to communication but rather as an essential component of the social and cultural identity of the Bugis community in South Bone.